Impact of primary tumor location on patterns of recurrence and survival of patients undergoing resection of liver metastases from colon cancer. Issue 1 (January 2020) - Russolillo, Nadia; Sperti, Elisa; Langella, Serena; Menonna, Francesca; Allieta, Andrea; Di Maio, Massimo; Ferrero, Alessandro
Abstract: Background: Several studies have described a worse prognosis for right-sided colon cancer compared to left-sided. The aim of this study was to compare patterns of recurrence and survival following resection of liver metastases (LM) from right-sided (RS) versus left-sided (LS) colon cancer. Methods: Patients undergoing resection for colon cancer LM between 2000 and 2017 were analyzed. Rectal cancer, multiple primaries and unknown location were excluded. Results: Out of 995 patients, 686 fulfilled inclusion criteria (RS-LM = 322, LS-LM = 364). RS colon cancer had higher prevalence of metastatic lymph nodes (67.4% vs. 57.1%, P  = 0.008). RS-LM were more often mucinous (16.8% vs. 8.5%, P  = 0.001) and G3 (58.3% vs. 48.9%, P  = 0.014). 451 (65.7%) patients experienced recurrence (RS-LM 68.9% vs. LS-LM 62.9%). In RS-LM group, recurrence was more often encephalic (2.3% vs. 0%, P  = 0.029) and at multiple sites (34.2% vs. 23.5%, P  = 0.012). The rate of re-resection was lower in RS-LM patients (27.9% vs. 37.5%, P  = 0.024). Multivariate analysis showed RS-LM to have worse 5-year overall (35.8% vs. 51.2%, P  = 0.002) and disease-free survival (26% vs. 43.6%, P  = 0.002). Conclusions: RS-LM is associated with worse survival and aggressive recurrences, with lower chance of re-resection.